Agroecology-based assembly and function of endophytic bacteria in seeds of Triticum aestivum - Prasad, Jogdande Sai; Suman, Archna; Kumar, Dharmendra; Sharma, Pushpendra; Ramakrishnan, B.; Aswini, K. (Frontiers in Microbiology, 2025)
The seed, a vital plant organ for its continuation, contains microbial endophytes that develop as part of the early plant microbiome and assist growing seedlings in various ways. In this study, bacterial endophytes from seeds of wheat cultivars grown under different agro-ecological conditions were genotypically and functionally analyzed. Despite environmental differences and cultivars adapted to distinct agroclimatic zones, the endophytic bacterial count ranged from 2.79 to 5.19 Log CFU/g. The dominant seed bacteria belonged to the phylum Firmicutes, with diverse members of the genus Bacillus. There were core and niche-specific bacteria among the different agroclimatic zones. The seed endophytic bacteria exhibited hydrolytic enzyme activities, mainly amylase, cellulase, and xylanase. The nitrogen fixation capacity ranged from 0.81 to 32.06 nmol ethylene h−1 mg−1 protein, while phosphate solubilisation ranged from 147 to 440 μg mL−1. Some seed endophytes from the North Western Plains Zone (NWPZ) showed strong antagonism toward Fusarium graminearum (52%), Bipolaris sorokiniana (35.9%), and Tilletia indica (43.4%). The green fluorescent protein (GFP)-tagged endophytic bacteria, when reintroduced to wheat seeds, were observed to colonize and migrate within germinating seedlings, Confirm their potential for internal establishment and movement within the host. These seed endophytic bacteria may offer notable benefits by colonizing root tissues during germination, thereby enhancing plant growth and yield.